Abraham's luggage: a social life of things in the medieval Indian Ocean world - Lambourn, Elizabeth (Asian connections, 2018)
From a single merchant's list of baggage begins a history that explores the dynamic world of medieval Indian Ocean exchanges. This fresh and innovative perspective on Jewish merchant activity shows how this list was a component of broader trade connections that developed between the Islamic Mediterranean and South Asia in the Middle Ages. Drawing on a close reading of this unique twelfth-century document, found in the Cairo Genizah and written in India by North African merchant Abraham Ben Yiju, Lambourn focuses on the domestic material culture and foods that structured the daily life of such India traders, on land and at sea. This is an exploration of the motivations and difficulties of maintaining homes away from home, and the compromises that inevitably ensued. 'Abraham's Luggage' demonstrates the potential for writing challenging new histories in the accidental survival of apparently ordinary ephemera